the Impact of Food Influencer References on Instagram and Youtube Platform on Behavioral Intention - Audinia Anggraeni; Daniel T H Aruan (Interdisciplinary Social Studies, 2025)
Indonesia's food and beverage industry is expanding quickly because to substantial potential and widespread internet use. Businesses in Indonesia are encouraged to deploy culinary influencers to leverage sosial media to engage customers. With regard to customer engagement efforts and consumer behavior in the food and beverage business, this study attempts to scientifically investigate the impact of perceived enjoyment, food influencer legitimacy, homophily, and interactivity. The Structural Equation Model (SEM) approach was applied using the SEMPLS 3.2.9 application to process 300 data points that were obtained from online surveys. The study's findings show that the factors perceived enjoyment, influencer credibility, and interaction have a favorable impact on consumer engagement. Additionally, it was discovered that food customer interaction positively impacted.